2016
DOI: 10.1002/jms.3781
|View full text |Cite
|
Sign up to set email alerts
|

Efficient approach for the detection and identification of new androgenic metabolites by applying SRM GC‐CI‐MS/MS: a methandienone case study

Abstract: Identification of anabolic androgenic steroids (AAS) is a vital issue in doping control and toxicology, and searching for metabolites with longer detection times remains an important task. Recently, a gas chromatography chemical ionization triple quadrupole mass spectrometry (GC-CI-MS/MS) method was introduced, and CI, in comparison with electron ionization (EI), proved to be capable of increasing the sensitivity significantly. In addition, correlations between AAS structure and fragmentation behavior could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The GC–MS behavior was studied with CI−GC−TQMS and LE−EI−GC−QTOF−MS. Earlier publications have pointed out that CI−GC−TQMS spectra of steroids contain more structural information and that CI leads to more predictable behavior in comparison with EI . For high‐resolution data, LE−EI−GC−QTOF−MS was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GC–MS behavior was studied with CI−GC−TQMS and LE−EI−GC−QTOF−MS. Earlier publications have pointed out that CI−GC−TQMS spectra of steroids contain more structural information and that CI leads to more predictable behavior in comparison with EI . For high‐resolution data, LE−EI−GC−QTOF−MS was used.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier publications have pointed out that CI−GC−TQMS spectra of steroids contain more structural information and that CI leads to more predictable behavior in comparison with EI. 29,35 For high-resolution data, LE−EI−GC−QTOF−MS was used. In general, LE−EI fragmentation behavior of AAS is similar to conventional EI (ie, 70 eV) behavior, but with higher abundances of the high m/z ions.…”
Section: Gc-ms Behavior Of Steroid Sulfatesmentioning
confidence: 99%
“…The detection protocol is explained in detail in a previous publication . To summarise: based upon the most common metabolic pathways of AAS in humans, a list of theoretically potential metabolites is generated.…”
Section: Methodsmentioning
confidence: 99%
“…This makes it worthwhile to reinvestigate the metabolism of these two AAS with another soft ionization technique that does not suffer from this ionization bottleneck. The aim of the study reported here was to search for new long‐term metabolites of oxymesterone and mesterolone by application of a gas chromatography–chemical ionization–triple quadrupole mass spectrometry (GC‐CI‐MS/MS) protocol for metabolite detection and identification . CI in combination with triple quadruple technology has proven to significantly increase the sensitivity for a wide range of compounds in comparison with electron ionization (EI) .…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been suggested and pursued to accomplish the goal of isolating long‐term metabolites of low abundance and/or unexpected composition in a complex matrix such as urine. One option has been the in silico prediction of structures of potential phase I metabolites of steroidal agents and the analysis of elimination studies with particularly sensitive analytical strategies . As an example, 32 potential metabolites of metandienone were considered for establishing a test method based on GC with chemical ionization (CI) and QqQ analyzer, where the expected precursor‐product ion pairs for each analyte were derived and predicted by structure similarity to earlier studied compounds .…”
Section: Anabolic Agentsmentioning
confidence: 99%